Role of verb in personification used in sharia economic topics on KONTAN news site - Muhammad Wahyudi; Yasir Riady (Mitra Palupi, 2021)
Background: The linguistic registers related to the aspects of sharia economic including their figurative language become a problem when the readers are not a native speaker of Bahasa Indonesia. Purpose: This study focuses on the personification in the news of sharia economy found on Kontan website. Design and methods: It is used descriptive analytical study to analyze the topics. There are 20 data analyzed in this article, most of articles from KONTAN new site in several information or headlines Results: The result of analysis shows the role of verb in personification adds more layers of meaning. The recontextualization also occurs consistently in this clause. This syntactic impact on semantic meaning is evidently caused by verb’s grammatical function in the clause since the verb governs the subject and the object in the clause. This role shows the effect on semantic meaning producing recontextualization. These more layers of context also expand the layers of meaning into secondary meaning and so on. The analysis shows the verb’s syntactic properties cause the expansion of meaning and multiple layers of contexts. The underlying cognitive mechanism of this process is the role of verb in syntax also shows the function as the cognitive reference point of human action. Therefore, the projection of human action onto non-animate objects like common bank and sharia bank can occur and become cognitively accessible.